Plant resistance against whitefly and its engineering - Li, Di; Li, Heng-Yu; Zhang, Jing-Ru; Wu, Yi-Jie; Zhao, Shi-Xing; Liu, Shu-Sheng; Pan, Li-Long (Frontiers in Plant Science, 2023)
Plants face constant threats from insect herbivores, which limit plant distribution and abundance in nature and crop productivity in agricultural ecosystems. In recent decades, the whitefly Bemisia tabaci, a group of phloem-feeding insects, has emerged as pests of global significance. In this article, we summarize current knowledge on plant defenses against whitefly and approaches to engineer plant resistance to whitefly. Physically, plants deploy trichome and acylsugar-based strategies to restrain nutrient extraction by whitefly. Chemically, toxic secondary metabolites such as terpenoids confer resistance against whitefly in plants. Moreover, the jasmonate (JA) signaling pathway seems to be the major regulator of whitefly resistance in many plants. We next review advances in interfering with whitefly-plant interface by engineering of plant resistance using conventional and biotechnology-based breeding. These breeding programs have yielded many plant lines with high resistance against whitefly, which hold promises for whitefly control in the field. Finally, we conclude with an outlook on several issues of particular relevance to the nature and engineering of plant resistance against whitefly.